PENGARUH ASSESSMENT FOR LEARNING TERHADAP KEMAMPUAN BERARGUMENTASI SISWA SEKOLAH MENENGAH ATAS - EKA RAKHMAWATI; MURNI RAMLI; MUZZAYYINAH MUZZAYYINAH; RADEN RARA SAPARTINI (BIO-PEDAGOGI, 2016)
The research aims to know the effect of Assessment for Learning (AfL) to argumentative skill of high school students. The  research used a quasi experimental design with nonequivalent control group design. The design consists of  control class and experiment class. Two clasess was randomly selected from 9 classes. The participants were 67 students from  grade 10 of one high school in Surakarta. Data of argumentative skill was a pre-post test of AfL. The hypothesis test using t test and paired sample t test. The results of hypothesis testing showed that the significant value gained 0.000 <0.05, therefore H0 is rejected or H1 is accepted. The effect of Assessment for Learning (AfL) to argumentative skill of high school students is the significantly different between control and experimental class